Hypertensive disorders of pregnancy and menopausal symptoms: a cross-sectional study from the data registry on experiences of aging, menopause, and sexuality. Issue 1 (January 2021) - Faubion, Stephanie S.; King, Amanda; Kattah, Andrea G.; Kuhle, Carol L.; Sood, Richa; Kling, Juliana M.; Mara, Kristin C.; Kapoor, Ekta
Abstract: Objective: Hypertensive disorders of pregnancy and menopausal symptoms, specifically vasomotor symptoms, have both been associated with cardiovascular disease risk in women. However, data are sparse on the association between these two female-specific cardiovascular risk factors. This study was conducted to investigate the association between a history of a hypertensive disorder of pregnancy and menopausal symptoms. Methods: This was a cross-sectional study of women aged 40 to 65 years seen for specialty consultation in women's health clinics at Mayo Clinic Rochester, MN and Scottsdale, AZ, between May, 2015 and September, 2019. A self-reported history of hypertensive disorders of pregnancy served as the independent variable, and menopause symptoms as assessed by the Menopause Rating Scale were the primary outcome measure. Results: Of 2, 684 women included in the analysis, 180 had a self-reported history of a hypertensive disorder of pregnancy. The total menopausal symptom scores as well as somatic and psychological domain scores were higher in women with a history of a hypertensive disorder of pregnancy compared to women without a history of a hypertensive disorder of pregnancy or to women without a pregnancy. On multivariable analysis, women with a hypertensive disorder of pregnancy using hormone therapy had significantly higher total menopause symptom scores than women with no such history. Conclusions: In this large cross-sectional study, a history of hypertensive disorders of pregnancy was associated with more bothersome menopausal symptoms. Additional study is needed to determine the strength of this association, underlying mechanisms of the association, and clinical implications for cardiovascular risk prediction in women.